Evaluation Of The Attitude Of Breastfeeding Of Covid-19 Survival During Self-Isolation Period - Vittria Meilinda (Institute of Computer Science (IOCS), 2021)
In Indonesia and the world are experiencing the Covid-19 Pandemic. During the postpartum period, breastfeeding is highly recommended because it has been shown to provide a very strong protective effect against infectious diseases by increasing the baby's immune system and in various studies that this virus has never been found in breast milk, so this is a way for mothers to continue breastfeeding their babies. by continuing to practice procedures to prevent mother-to-child transmission of infection. The purpose of this study was to find out in depth the attitude of breastfeeding mothers who survived COVID-19 during the self-isolation period. Qualitative research methods directly to 30 informants, with a phenomenological study approach. Data was collected through observation and in-depth interviews. The data were analyzed using Interpretative Phenomenological adjusted to the size of the Guide for Breastfeeding Mothers (who are in Self-Isolation) during the Covid-19 Pandemic of the Indonesian Ministry of Health. The results of research conducted during the pandemic in 2020 showed positive and negative attitudes from breastfeeding mothers in the care of babies carried out, breastfeeding babies with Covid transmission prevention procedures, support from health workers and problems faced during self-isolation.